Reducing SMPS Size and Losses with a Novel Piezoelectric EMI Filter - Hubert, Florian; Kübrich, Daniel; Dürbaum, Thomas; Rupitsch, Stefan J. (CIPS 2024 - International Conference on Integrated Power Electronics Systems, 2024)
Switch-mode power supplies (SMPS) represent a main contributor of electromagnetic interference (EMI). Reducing the EMI filter size with minimal effort is a complex challenge for SMPS developers. To tackle this challenge, we present a new EMI filter concept based on the piezoelectric effect. By utilizing several mechanical vibration modes, multiple disturbance peaks of an interference spectrum can be suppressed. For demonstration purpose an optimized piezoelectric EMI filter is implemented in a flyback converter and the EMI suppression is investigated. In the experiment, a 36 % lower DC loss and a 55 % volume reduction could be achieved by substituting a conventional Y-capacitor with a piezoelectric EMI filter.<br